Preliminary assessment of serum capillary zone electrophoresis in the Asian elephant (Elephas maximus) - Osorio, Shirley; Soto, Jeny; Schmitt, Dennis; Kiso, Wendy; Cray, Carolyn (Frontiers in Veterinary Science, 2023)
Serum protein electrophoresis has been demonstrated to have utility in diagnostic workup, wellness exams, and prognosis. Agarose gel electrophoresis (AGE) has previously been described for use with serum from Asian elephants (Elephas maximus). As the newer method of capillary zone electrophoresis (CZE) is becoming more commonplace in veterinary diagnostic laboratories, serum samples from Asian elephants were examined using this method. CZE allowed for a reproducible definition of two beta fractions and, overall, showed a low coefficient of variation for fraction quantitation. Preliminary reference intervals were generated using samples primarily from an older population of 22 female elephants. Albumin levels determined by CZE were also compared with those determined by the bromocresol green method on a chemistry analyzer. It was found that the latter method overestimated the level of albumin with a mean positive bias of 11.6% or 0.38 g/dL, thus method-specific reference intervals should be used. Significant negative correlations were observed between A/G ratio determined by CZE and serum amyloid A levels (r = −0.47, p < 0.0001) and haptoglobin (r = −0.52, p < 0.0001); both APP were significantly correlated with the alpha 2 globulin fraction (p < 0.0001). CZE reflects an overall picture of changes in acute phase proteins and immunoglobulins and accurate quantitation of albumin and thus should be considered as an adjunct tool to the use of other measures of the acute phase response in patient monitoring.